Representation of real numbers by Fibonacci sequence - Tokmakova, Iryna Anatoliyivna (НТУ "ХПІ", 2019)
The paper deals with imaging of real numbers by the Fibonacci sequence. An algorithm for changing from decimal representation of a number to its F−image is developed. The application of the algorithm is demonstrated by considering several specific examples. The correlation between binary numbers and numbers given as their F−images is analyzed.

У даній роботі описано зображення дійсних чисел за допомогою послідовності Фібоначчі. Запропоновано алгоритм переходу від десяткового представлення числа до F-зображення. Продемонстровано дію алгоритму на декількох конкретних прикладах. Проаналізовано звʼязок двійкового зображення з F-зображенням дійсного числа.
Зображення дійсних чисел з допомогою послідовностей Фібоначчі
Keywords: recurrence formulae; decimal number system; binary number system; system; рекурентні співвідношення; десяткова система числення; двійкова система числення